Teacher-Student Consultation as an Oral Device to Improve Speaking Skill - Sri Hastati; Badruddin Kaddas (South Sulawesi Education Development (SSED), 2023)
This study shows how consultation improves students' speaking skills and how SD Inpres Bertingkat Mamajang 1 Kota Makassar third graders are interested in using it. The problem statements were 1) Does teacher-student consultation improve students' speaking skills? and 2) What are students' interests in using consultation? The research aimed to test the use of consultation as an oral device to improve students' speaking skills and describe their interest in it. Consultation was used to discuss learning difficulties and how to improve English, while the speaking test focused on accuracy in grammar, pronunciation, and vocabulary; fluency in terms of no time spent researching further words; and comprehensibility in terms of students' ability to understand and be understood. The research used a pre-experimental method with one group pre-test and post-test and two data collectors: a speaking test and a questionnaire to assess students' speaking skills in pre- and post-tests and their interest in using consultation as an oral device. A Likert attitude scale was used to analyze speaking test and questionnaire data. The speaking test and questionnaire were taken from 30 third-grade A1 students at SD Inpres Bertingkat Mamajang 1 Kota Makassar in 2022/2023. The descriptive analysis showed that students' speaking accuracy improved from poor (2,6) to average (3,6) and fluency improved from average (16) to average (17) with mean scores 3,367. Students' speaking comprehensibility improved from poor (2,667) to average (3,467). Students' interest in consultation was high (mean score 79,175). Accuracy, fluency, and comprehensibility T-test values were greater than T-table 1,70. It suggested consultation could improve students' speech. There was evidence that consultation improves students' speaking skills and that they are highly interested in it as an oral device.